Will refugees also get vaccinated against COVID-19 in Africa? - Abdulmumin Damilola Ibrahim; Adigizi Iliya Akpus; Abdullahi Tunde Aborode; Abdulhammed Opeyemi Babatunde (Elsevier, 2021)
Africa has the second-highest number of displaced persons in the world. This number increases continuously due to the ongoing crisis in different countries in sub-Saharan Africa. African refugees are not only prone to COVID-19 but they are also capable of transmitting it across country borders. This article aims to highlight the need for equity in vaccine distribution in Africa to include refugees in each host countries.